Valo Ja Aine. (Helsinki : Helsinki Art Museum, 1987)
Vavén, Kari ; Enckell, Carolus ; Eskola, Lea ; Gebhard, Hannu ; Hiekka, Urho ; Havaoja, Paulo ; Jamsa, Martti ; Kanervo, Marja ; Kiljunen, Satu ; Kojima, Hiroyoshi ; Korhonen, Auli ; Korhonen, Juha Pekka ; Kukkasjarvi, Irma ; Lavonen, Maija ; Lukander, Minni ; Luukela, Annikki ; Lotjonen, Matti ; Minkkinen, Eila ; Nordstrom, Lars-Gunnar ; Pohjolainen, Pauno ; Popovits, Zoltan ; Paakkonen, Markku ; Riska, Kristina ; Rummukainen, Petri ; Salo, Markku ; Surjanen, Harri ; Takala, Kimmo ; Tanttu, Wille ; Toikka, Oiva ; Varis, Hanna ; Vika, Sakari ; Wirkkala, Maaria
Valo Ja Aine / Ljus och Materie / Light and Material, Helsingin Kaupungin Taidemuseo, Helsinki (Helsinki Art Museum), 8.11.1987 - 28.2.1988. The exhibition was arranged in honour of the 70th anniversary of Finland's independence.
Engels & Fins
kunstcatalogus